Nursing monitoring of the discipline of semiology and semiotechnology: an experience report (Research, Society and Development, 2021)
The monitoring is an activity that provides an opportunity for the student-monitor to participate in theoretical and practical moments with the students in order to deepen the content and in search of a development associated to the teaching practice. The discipline of Semiology and Semiotechnology, on its part, covers the technical procedures performed in the laboratory and throughout the life of the professional nurse. However, the monitor becomes a facilitator of the other student's acquisition of knowledge. The present study aims at reporting on the experience of the Semiology and Semiotechnology monitoring by undergraduate students of the nursing course of the Cristo Faculdade do Piauí. This is a descriptive study, of the experience report type. The monitoring occurred from August to December 2020, corresponding to the semester 2020/2. These were moments through the remote platform Google Meet in front of the participating students. The moments of monitoring provided the creation of bonds between the monitors and students benefited by the monitoring program, and this facilitated the teaching-learning process of the subject in question. Through the continuous review of the contents, it was possible to create a solid base of knowledge, as well as the constant search for updated information and the use of technology, thus inferring the great importance of the monitoring program for the students of the university. The experience represented a relevant activity for the monitors, since it allowed for academic, professional, and personal growth, as well as several gains for the participating public.